PERAN PEMERINTAH DESA DALAM PELAKSANAAN TUGAS MEMBERDAYAKAN PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) SEBAGAI LEMBAGA KEMASYARAKATAN DESA DI DESA SIMANDOLAK KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI TAHUN 2022 - Harisa, Listia Ningsih; ', Wazni, (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Village Government is a Government Institution whose duties at the Village level are regulated through Government regulations. In the field, we found several problems in the Simandolak Village PKK, namely POKJA 2 and 3 had not yet been implemented and there were still weaknesses in the administration of the PKK. This research was conducted to see the role of the Simandolak Village Government in the Simandolak Village PKK and to determine the supporting and inhibiting factors in the implementation of the PKK in Simandolak Village. This research uses Ryaas Rasyid's role theory which consists of three indicators, namely: the role of regulator, dynamist and facilitator. This type of research is descriptive. This research location is divided into primary data and secondary data in the form of archives and village data as well as PKK data from Simandolak Village, Benai District, Kuantan Singingi Regency. The results of this research show that the role of the Simandolak Village Government, Benai District, Kuantan Singingi Regency is: (1) The role of the Village Government Regulator in making Village Regulations regarding LKD and Decrees on Determining Management of the PKK Driving Team. (2) The role of the Dinamisator is to provide technical guidance to increase the capacity of PKK cadres, provide technical guidance for anti-narcotics activists, and provide guidance on PKK administration. However, for administering the PKK in Simandolak Village, there are still weaknesses in administering the PKK. (3) The role of the Simandolak Village Government Facilitator as Resource Person, Trainer, Monitoring, Motivator and providing funds for the implementation of the PKK work program. Supporting indicators for the level of Village Government participation in empowering the PKK and Cooperation between the Village Government, the PKK Mobilization Team and the Community. Meanwhile, the inhibiting factors are budget funds and limited budget funds. Keywords: Role of Government, Regulator, Dynamist, Facilitator